THE ROLE OF LEGAL AID ORGANIZATIONS (OBH) UNDERSTAND RIAU IN RESOLVING CHILDREN'S CASES IN PEKANBARU CITY - M. Alpi Syahrin, Al Fikri Lubis, Al Mario, Try Muhammad (NOMOI Law Review, 2020)
Crimes are not only committed by adults against children, but there are also crimes committed by children. Crimes involving children often end up in court, and there are some differences that courts make when a child sits as a convict. Children facing the law, whether children conflict with the law (Bad Boy), Victim's Child, or Witness's Child, must be provided legal assistance and accompanied by legal aid or legal counsel. Thus, there is a need for special assistance to ABH, to ensure the psychology of the child is not compromised. Legal aid organizations that are required to assist ABH both outside and in the trial, also play a role in ABH's psychological assistance. OBH PAHAM Riau is present in the effort to fight for the guarantee and protection of the rights of marginalized/poor people as well as the enforcement of fair laws specifically in pekanbaru city, Riau.Keywords: Role, OBH PAHAM Riau, Children's Case.